Good Corporate Governance and Integrity of Financial Statement - Ramadhini Iskandar, Anggya (Jurnal Indonesia Sosial Sains, 2023)
This research aims to find out any influences of Audit Quality, Industry Specialized Auditors, and Audit Fee toward Financial Statement Integrity as well as Good Corporate Governance as an intervening variable. Populations used on this research are companies in mining sectors that have been listed in Bursa Efek Indonesia (BEI) from 2018-2021. This research has 36 companies with a total of 144 samples, all of them already eligible for purposive sampling. This research is analyzed using Structural Equation Model (SEM) powered by Analysis of Moment Structures (AMOS). This research’s hypothetical results suggest that audit qualities affect good corporate, audit fee, and good corporate governance. Hence, it also affects the financial statement integrity overall. This research also suggests audit quality and industry specialized auditor do not affect the financial statement integrity. Industry specialized auditor and audit fee also do not affect good corporate governance.